Obesity, food intake and exercise: Relationship with ghrelin - Tiryaki-Sonmez Gul; Vatansever Serife; Olcucu Burcin; Schoenfeld Brad (Sciendo, 2015)
Obesity, a disorder of body composition, is defined by a relative or absolute excess of body fat. In general adult population, obesity has been associated with a diverse array of adverse health outcomes, including major causes of death such as cancer, diabetes, cardiovascular disease, as well as functional impairment from problems such as osteoarthritis and sleep apnea. Ghrelin is a newly discovered peptide hormone which plays an important role in obesity. It is a powerful, endogenous orexigenic peptide and has a crucial function in appetite regulation, as well as short - and long-term energy homeostasis. In the presence of increased obesity, decreased physical activity, and high food consumption, the relationship between exercise, appetite, food intake and ghrelin levels has important implications. In this review, we discuss the effect of acute and chronic exercise performance on appetite, food intake and ghrelin and their relationships.